Asphalt compositions and methods of making same
By mixing the chloroprene-based polymer latex with asphalt and modifying it at room temperature, the problem of insufficient oil resistance of asphalt in the prior art is solved, and the oil resistance of the asphalt composition is significantly improved and the energy cost is reduced.
Patent Information
- Application Number
- CN202380058284.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-12-28
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has shortcomings in improving the oil resistance of asphalt, especially in the balance between energy efficiency and oil resistance.
By mixing a specific amount of chloroprene-based polymer latex with asphalt and modifying it at room temperature, an asphalt composition with excellent oil resistance was prepared.
The oil resistance of the asphalt composition is achieved significantly improved, energy costs are reduced, and durability of the asphalt pavement is improved.
Smart Images

Figure BDA0005263371580000101
Abstract
Description
Technical Field
[0001] The present invention relates to an asphalt composition having excellent oil resistance and a method for producing the same. Background Art
[0002] Asphalt used in road paving is composed of hydrocarbon components, so it softens when it comes into contact with oil or fuel leaking from vehicles running on the road. If a vehicle passes through a softened paved road surface, the road surface in that part will peel off and become a collapsed state called a pit, which may hinder the vehicle's travel. Therefore, in order to improve the durability of paved roads, asphalt is required to have improved oil resistance.
[0003] Therefore, if chloroprene, which is excellent in oil resistance, can be added to asphalt to impart oil resistance, it can be expected to contribute to improving the durability of the road surface.
[0004] In addition, asphalt for road paving is modified with a polymer for the purpose of imparting elasticity at high temperatures and brittleness resistance at low temperatures.
[0005] For example, Patent Document 1 discloses that heated asphalt is modified with polyamide to impart oil resistance to the asphalt.
[0006] Patent Document 2 discloses that asphalt emulsion is modified by using chloroprene latex.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 4580457
[0010] Patent Document 2: Japanese Patent No. 5897522 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, in the method of Patent Document 1, since a long period of heating is required in order to uniformly mix the asphalt and the polymer when the asphalt is heated and reformed with the polymer, there is a problem of increased energy cost.
[0013] Furthermore, the method of Patent Document 2 is a technique for imparting elongation to asphalt emulsion and does not suggest any improvement in oil resistance.
[0014] As such, a composition having improved oil resistance is desired for asphalt for road paving.
[0015] Means for solving problems
[0016] The present inventors have found that by using a specific amount of chloroprene polymer latex together with asphalt, an asphalt composition having excellent oil resistance and suitable for road paving can be obtained. In addition, they have found that by modifying the asphalt at room temperature using a specific method, the energy cost can be kept low, thereby completing the present invention.
[0017] [1] An asphalt composition comprising asphalt and a chloroprene polymer,
[0018] The content of the chloroprene polymer is 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the asphalt solid content, and the amount of the tetrahydrofuran-insoluble component of the chloroprene polymer is 20% by mass or more and 90% by mass or less.
[0019] [2] A method for producing an asphalt composition, characterized in that an asphalt emulsion and a chloroprene latex containing a chloroprene polymer in which the amount of tetrahydrofuran-insoluble components of the chloroprene polymer is 20 mass % or more and 90 mass % or less are mixed, wherein the mixing amount of the chloroprene latex is calculated as follows: the amount of the chloroprene polymer is 5 mass parts or more and 20 mass parts or less per 100 mass parts of the asphalt solid content in the asphalt emulsion.
[0020] [3] A method for producing an asphalt composition, comprising mixing an aqueous surfactant solution and chloroprene latex (the chloroprene latex contains a chloroprene polymer, the amount of tetrahydrofuran-insoluble components of the chloroprene polymer being 20% by mass or more and 90% by mass or less) obtained by mixing at 5 to 40° C. with molten asphalt, and emulsifying the mixture using a colloid mill, wherein the amount of chloroprene latex is 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the asphalt solids, calculated as solid content.
[0021] [4] The method for producing a composition according to [2], wherein the asphalt emulsion and the chloroprene latex are mixed at 5 to 40°C.
[0022] [5] The method for producing a composition according to [2] or [3], wherein the chloroprene latex used is a latex that is stable in an emulsified state at pH 2 to 4.
[0023] [6] A method for producing a mixture, comprising the step of mixing the composition produced by the production method of [2] or [3] and an aggregate.
[0024] [7] A method for producing an asphalt pavement, comprising the step of spreading and drying the composition produced by the production method of [2] or [3].
[0025] [8] A method for producing an asphalt pavement, comprising pouring a mixture obtained by the production method of [6].
[0026] [9] A mixture comprising the composition of [1] and an aggregate.
[0027]
[10] An asphalt pavement obtained by spreading the composition of [1] and drying it.
[0028]
[11] An asphalt pavement formed by pouring the mixture of [9].
[0029] Effects of the Invention
[0030] If used for paving purposes, it can impart oil resistance to the asphalt construction surface, thereby enabling paving with improved durability. DETAILED DESCRIPTION
[0031] A mode for carrying out the present invention will be described.
[0032] The present embodiment is constituted of an asphalt composition, a method for producing the asphalt composition, and uses of the composition.
[0033] Asphalt composition
[0034] The asphalt composition of this embodiment contains asphalt and a chloroprene polymer, wherein the chloroprene polymer accounts for 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the asphalt solid content, and the amount of tetrahydrofuran-insoluble components of the chloroprene polymer is 20% by mass or more and 90% by mass or less.
[0035] The chloroprene copolymer is preferably 5 parts by mass or more and 20 parts by mass or less, and more preferably 7 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the asphalt solid content. Within this range, an asphalt composition having high oil resistance can be obtained.
[0036] The composition contains a dispersion medium as required, specifically, water, alcohol, etc., and the amount thereof is not particularly limited as long as it is an amount that can be easily stored, moved, applied, etc., and the dispersion medium is preferably contained in an amount of 10 to 500 parts by mass relative to 100 parts by mass of the solid matter (the total amount of asphalt and chloroprene polymer) in the composition.
[0037] The dispersion medium may be a medium used in chloroprene latex and asphalt emulsion.
[0038] <Asphalt>
[0039] Asphalt can be used without particular limitation, for example, straight asphalt, blown asphalt, semi-blown asphalt, natural asphalt, modified asphalt, desolventized asphalt, tar, asphalt (pitch) and other asphalt materials, A, B and C heavy oils, etc. These are usually dispersed in the presence of a dispersant using water as a dispersion medium and used in the form of an emulsion (asphalt emulsion). The dispersant is not particularly limited, and cationic dispersants, anionic dispersants, etc. can be used, and cationic dispersants are more preferred.
[0040] Specific examples of cationic dispersants include mixtures of amines and acids. Amines include primary amines, secondary amines, tertiary amines, aliphatic diamines, etc. Among these, amines having an alkyl group are more preferred.
[0041] Examples of the primary amine include laurylamine, myristicamine, 1-amino-3-undecyloxy-propane, cetylamine, stearylamine, oleylamine, behenylamine, etc. Alternatively, examples include compounds in which the hydroxyl group of a compound having a hydroxyl group such as coconut oil, soybean oil, beef tallow, hardened beef tallow, etc. is replaced by an amino group.
[0042] Examples of the tertiary amine include dimethyllaurylamine, dimethylstearylamine, dimethylmyristylamine, and tertiary amines in which a hydroxyl group in a compound having a hydroxyl group such as coconut oil and hardened beef tallow is replaced by a dimethylamino group.
[0043] Specific examples of the anionic dispersant include rosin acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, sodium salt of dodecylsulfuric acid, and the like.
[0044] These may also be mixed and used in two or more kinds. The amount of these dispersants used is not particularly limited. Generally speaking, by adding 0.2 mass parts or more and 0.5 mass parts or less relative to 100 mass parts of the solid content contained in the asphalt, the asphalt can be necessarily and fully dispersed in water. In addition, nonionic surfactants may also be used, and compounds having a polyoxyalkylene structure described later may also be used as dispersants.
[0045] <Chloroprene-based polymer>
[0046] The chloroprene polymer may be a polymer obtained by polymerizing a 2-chloro-1,3-butadiene monomer (A-1) (hereinafter also referred to as a "chloroprene monomer") alone, or may be a polymer obtained by copolymerizing the chloroprene monomer (A-1) and a monomer (A-2) copolymerizable with chloroprene.
[0047] The monomer (A-2) copolymerizable with chloroprene is not particularly limited unless the purpose of the present invention is impaired, and examples thereof include 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid and its esters, methacrylic acid and its esters, and sulfur. Among these, 2,3-dichloro-1,3-butadiene and 1-chloro-1,3-butadiene are preferred, and 2,3-dichloro-1,3-butadiene is more preferred.
[0048] The content of the monomer copolymerizable with chloroprene is preferably in the range of 0 to 20 parts by mass based on 100 parts by mass of 2-chloro-1,3-butadiene (chloroprene) (A-1).
[0049] The monomer copolymerizable with chloroprene may be used alone or in combination of two or more.
[0050] The tetrahydrofuran-insoluble content of the chloroprene polymer is 20% by mass or more and 90% by mass or less. It is preferably 20% by mass or more and 80% by mass or less, and more preferably 30% by mass or more and 50% by mass or less. If it is within this range, the fluidity as an asphalt composition can be obtained, so it is preferred.
[0051] Chloroprene polymers are usually used in the form of chloroprene latex. Chloroprene latex is a material obtained by emulsifying a lipophilic chloroprene polymer with an emulsifier and dispersing it in water in the form of particles.
[0052] The method for producing the chloroprene latex is not particularly limited, but emulsion polymerization is preferred, and aqueous emulsion polymerization is particularly preferred industrially.
[0053] As the emulsifier for emulsion polymerization, an anionic surfactant, a nonionic surfactant or a protective colloid system such as polyvinyl alcohol is preferred.
[0054] Specific examples of the anionic surfactant include rosin acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, sodium salt of dodecylsulfuric acid, and the like.
[0055] Specific examples of the nonionic surfactant include polyoxyethylene alkyl ethers, sorbitan fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0056] When using rosin acid soap as an emulsifier, the amount of rosin acid soap used is preferably 3 to 8 parts by mass, more preferably 3 to 5 parts by mass, based on 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with the chloroprene monomer, in terms of rosin acid.
[0057] When the amount is 3 parts by mass or more, sufficient emulsification is achieved, the polymerization heat generation can be highly controlled, and the formation of agglomerates is suppressed, thereby obtaining an excellent product appearance.
[0058] The occurrence of the above-mentioned problem can be suppressed even in a system in which 3 parts by mass or less of rosin acid is emulsified by adding a dispersant such as sodium naphthalenesulfonate and a formaldehyde condensate.
[0059] As the polymerization initiator, a common free radical polymerization initiator can be used. For example, in the case of emulsion polymerization, common organic or inorganic peroxides such as benzoyl peroxide, potassium persulfate, and ammonium persulfate; and azo compounds such as azobisisobutyronitrile can be used. At the same time, a cocatalyst such as anthraquinone sulfonate or potassium sulfite, sodium sulfite, etc. can be used appropriately.
[0060] Generally, in order to obtain a copolymer having a desired molecular weight and distribution in the production of chloroprene latex, a molecular weight regulator (chain transfer agent) may be used during polymerization. For example, dithioalkyl xanthate represented by O,O-diisopropyl dithiobis(thioformic acid) ester and alkyl mercaptan represented by n-dodecyl mercaptan may be used, but the present invention is not limited to these.
[0061] Generally, in order to obtain a polymer having a desired molecular weight and distribution in the manufacture of chloroprene latex, a polymerization terminator is added to terminate the reaction when a predetermined polymerization rate is reached. There is no particular limitation on the polymerization terminator, and commonly used terminators include phenothiazine, p-tert-butylcatechol, hydroquinone, hydroquinone monomethyl ether, diethylhydroxylamine, and the like.
[0062] As the chloroprene latex, it is preferable to use a latex having a stable emulsified state at pH = 2 to 4.
[0063] <Compound Having Polyoxyalkylene Structure>
[0064] The asphalt composition of the present embodiment may contain a compound having a polyoxyalkylene structure. By containing the compound, the film-forming property when the asphalt composition is spread is improved, and a uniform coating film can be formed.
[0065] The compound having a polyoxyalkylene structure is not particularly limited as long as the above-mentioned effects can be obtained, and various compounds can be used regardless of molecular weight, hydrophobicity, etc.
[0066] As the compound having a polyoxyalkylene structure, for example, nonionic surfactants such as polyethylene glycol having ethylene glycol as a unit structure and polyoxyalkylene alkyl ethers can be used.
[0067] Specific examples of the compound having a polyoxyalkylene structure include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene alkyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyalkylene alkyl ether, polyoxyphenylene distyrenated phenyl ether, polyoxyethylene tribenzylphenyl ether, polyoxyethylene polyoxypropylene glycol, polyoxyalkylene alkenyl ether, polyoxyethylene nonylphenyl ether, and polyoxyethylene alkyl ether. Phosphate esters, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan tetraoleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene hardened castor oil, polyoxyethylene alkylamines, etc.
[0068] The compound having a polyoxyalkylene structure may be used alone or in combination of two or more.
[0069] The compound having a polyoxyalkylene structure may be synthesized or commercially available. Examples of commercially available compounds include Emarugen 103, 104P, 106, 108, 109P, 120, 123P, 130K, 147, 150, 210P, 220, 306P, 320P, 350, 404, 408, 409PV, 420, 430, 705, 707, 709, 1108, 1118S-70, 1135S-70, 1150S-60, 20 20G-HA, 2025G, LS-106, LS-110, LS-114, MS-110, A-60, A-90, B-66, PP-290, ラテムルPD-420, PD -430, PD-430S, PD450, SP-L10, AS-10V, AO-10V, AO-15V, TW-L120, TW-L106, TW-P120, T W-S120V, TW-S320V, TW-O120V, TW-O106V, TW-IS399C, TW-L120, 430V, 440V, 460V, MS-5 0. MS-60, MO-60, MS-165V, ECM1112, 3199V, 3299V, 3299RV, 4110, CH-25, CH-40, CH-60(K) , Aminol 102, 105, 105A, 302, 320, Aminol PK-02S, L-02, Homogeneol L-95 (all manufactured by Kao Corporation); ADEKA PLUNKO (registered trademark) L-23, 31, 44, 61, 62, 64, 71, 72, 101, 121, TR-701, 702, 704, 913R (all manufactured by ADEKA Co., Ltd.), etc.
[0070] As the compound having a polyoxyalkylene structure, a compound represented by the following formula (1) is preferred.
[0071] R1O-(CR2R3O) n -(CR4R5CR6R7O) m -(CR8R9CR 10 R 11 CR 12 R 13 O) l -(CR 14 R 15 CR 16 R 17 CR 18 R 19 CR 20 R 21 O). -(CR 22 R 23CR 24 R 25 CR 26 R 27 CR 28 R 29 CR 30 R 31 O) p -R 32
[0072] …Formula (1)
[0073] In formula (1), R1 is a hydrocarbon group having 6 to 20 carbon atoms, R2 to R 31 are each independently a group selected from a hydrogen atom, a methyl group and an ethyl group, R 32 It is a hydrogen atom or SO3M, wherein M is a hydrogen atom, Na, K, NH4, or NH(CH2CH2OH)3, and n, m, l, o and p are each independently an integer represented by 0 to 50, wherein n+m+l+o+p is an integer represented by 3 to 50, and there is no particular restriction on the arrangement order of the repeating units.
[0074] In the formula (1), the hydrocarbon group represented by R1 may be linear, branched or cyclic, and may be a saturated hydrocarbon group or an unsaturated hydrocarbon group.
[0075] R1 is preferably a hydrocarbon group having 2 to 18 carbon atoms, more preferably a hydrocarbon group having 6 to 14 carbon atoms, and still more preferably a hydrocarbon group having 6 to 11 carbon atoms. R1 is preferably a linear hydrocarbon group.
[0076] As R2~R 31 , are each independently preferably a methyl group or a hydrogen atom, more preferably a hydrogen atom.
[0077] R 32 When it is SO3M, M is preferably a hydrogen atom, Na, K, or NH4, and more preferably Na or K.
[0078] As n, m, l, o and p, each independently is preferably 1 to 30 (wherein n+m+l+o+p is 3 to 30), more preferably 1 to 20 (wherein n+m+l+o+p is 3 to 20), further preferably 1 to 10 and n+l+o+p=0 (wherein n+m+l+o+p is 3 to 10), particularly preferably 1 to 5 and n+l+o+p=0 (wherein n+m+l+o+p is 3 to 5).
[0079] The content of the compound having a polyoxyalkylene structure is preferably 0.1 to 5.0 parts by mass, more preferably 1.0 to 4.5 parts by mass, and even more preferably 2.0 to 4.0 parts by mass, based on 100 parts by mass of the solid content of the polychloroprene latex.
[0080] When the content of the compound having a polyoxyalkylene structure is within the above range, a stabilizing effect of the mixture can be obtained, the film-forming property when the asphalt emulsion is spread is good, and a uniform coating film can be obtained.
[0081] The asphalt composition may contain other compounding ingredients as required.
[0082] For example, inorganic fillers such as zinc oxide, calcium carbonate or silicon dioxide may be contained. When an inorganic filler is used, the amount of the inorganic filler may be 30% to 45% by mass, when the total amount of the asphalt, the chloroprene polymer and the inorganic filler is taken as 100% by mass.
[0083] The asphalt composition may also be mixed with a coagulant to promote solidification during drying. The coagulant is an aqueous solution of various polyvalent metal salts, and is an auxiliary agent used to reduce the dispersion stability of the asphalt emulsion and cause the asphalt to solidify and precipitate. The polyvalent metal salt used as the coagulant is preferably a coagulant that is easily water-soluble and has excellent coagulation performance for the asphalt composition, and examples thereof include calcium chloride, calcium nitrate, alum, and the like. When the coagulant is mixed with the asphalt composition, if the amount of the inorganic filler added is in the range of 10 to 30 parts by mass, when the total amount of the asphalt and the chloroprene polymer and the total amount of the coagulant are taken as 100 parts by mass, the asphalt composition can be solidified in a short time, and the precipitation of the coagulant on its surface can be prevented.
[0084] Method for producing asphalt composition
[0085] The method for manufacturing an asphalt composition of the present embodiment is characterized in that an asphalt emulsion and chloroprene latex are mixed, and the mixing amount of the chloroprene latex is calculated as follows in terms of solid content: relative to 100 parts by mass of asphalt solid content in the asphalt emulsion, the chloroprene polymer in the chloroprene latex is greater than 5 parts by mass and less than 20 parts by mass (first method).
[0086] The mixing method is not particularly limited, and a known mixing method can be used. The asphalt emulsion and the chloroprene latex are preferably mixed at 5 to 40° C. Good mixing can be achieved by mixing at this temperature.
[0087] The method for producing an asphalt composition according to the present embodiment is characterized in that the surfactant aqueous solution and chloroprene latex obtained by mixing at 5 to 40° C. are mixed with the molten asphalt and emulsified using a colloid mill. (Second method)
[0088] Examples of the surfactant include the surfactants exemplified as the dispersants used in the above-mentioned asphalt. The concentration thereof is adjusted so as to achieve the same dispersant concentration in the asphalt emulsion as in the above-mentioned first method.
[0089] When a compound having a polyoxyalkylene structure is used as a surfactant, it is not necessary to add it during production, but it can be added during the above mixing as necessary.
[0090] In the above production method, the energy cost when producing the asphalt composition can be suppressed to a low level.
[0091] When the composition of the present embodiment described above is dried, a chloroprene-modified asphalt composition can be obtained.
[0092] <Mixture>
[0093] The mixture of this embodiment contains the above-mentioned composition and aggregates. This mixture is called asphalt composite.
[0094] The method for producing a mixture according to the present embodiment includes a step of mixing the composition produced by the above-described production method and an aggregate.
[0095] For example, the asphalt composite material can be obtained by heating and melting the asphalt composition and mixing the aggregate. Alternatively, the asphalt composition of the present embodiment may be directly mixed with the aggregate and then heated.
[0096] The aggregate is not particularly limited, and crushed stone, pebbles, sand and gravel, recycled aggregate, ceramics, etc. may be selected and used.
[0097] There is no particular restriction on the amount of aggregate and the ratio to the total amount of asphalt and chloroprene polymer. When using aggregate, the aggregate is preferably 85 to 97 parts by mass, more preferably 90 to 97 parts by mass, based on 100 parts by mass of the total amount of asphalt, chloroprene polymer and aggregate. The aggregate can be mixed when used.
[0098] <Asphalt paving>
[0099] The composition of this embodiment can be used for asphalt paving that can be spread on a paved road surface.
[0100] As such paving, it can be used for spray sealing, or a seal layer of aggregate after spreading, etc. When the existing asphalt surface is removed for reuse, it can be used for cold in place recycling (CIR) paving, where the crushed asphalt is mixed as a regeneration agent and returned to the original place, or a roadbed regeneration construction method where the road surface is crushed at the existing location, the asphalt composition is mixed with the existing roadbed material, and the compaction is stabilized to re-form the roadbed.
[0101] The coating method may be to mix aggregates with the asphalt composition and pour the mixture. Furthermore, the asphalt composite formed by the mixture may be heated, melted, and poured to lay the asphalt. These construction methods may also be slurry seal, cold in-place recycling (CIR), roadbed recycling, etc.
[0102] When the asphalt composition of this embodiment is used, construction can be performed at room temperature.
[0103] The method for producing an asphalt pavement according to the present embodiment includes a step of spreading and drying the composition produced by the above-described production method.
[0104] Furthermore, in the method for producing an asphalt pavement according to the present embodiment, the mixture produced by the above-described production method is poured.
[0105] Example
[0106] The present invention is further described in detail below by way of examples, but the present invention is not limited to these examples.
[0107] [Example 1]
[0108] Into a glass reactor having an internal volume of 5 liters, 1.92 kg of 2-chloro-1,3-butadiene (manufactured by Tokyo Chemical Industry Co., Ltd.), 60 g of methacrylic acid, 20 g of 2,3-dichloro-1,3-butadiene, 2.1 kg of pure water, 80 g of polyvinyl alcohol (manufactured by Kuraray Co., Ltd., trade name PVA-205), 12 g of n-dodecyl mercaptan (molecular weight adjustment), and 12 g of N-lauric acid ethanolamide (manufactured by Toho Chemical Co., Ltd., trade name Tohoul N-230) were charged and emulsified, and then potassium persulfate (first-class product manufactured by Wako Pure Chemical Industries, Ltd.) was added as a polymerization initiator, and polymerization was carried out at a temperature of 45° C. in a nitrogen atmosphere. When the polymerization conversion rate of the monomer was confirmed to be 100%, an emulsion of phenothiazine was immediately added to terminate the polymerization, thereby obtaining a chloroprene latex. Subsequently, the unreacted monomers were removed by steam distillation. The solid content of the polychloroprene latex actually measured was 46.3% by mass. Table 1 shows the monomer charge ratio of each component converted into mass %.
[0109] 3 parts by mass of Emalgen 1135S-70 (manufactured by Kao Corporation) was added as a compound having a polyoxyalkylene structure to 100 parts by mass of the synthesized chloroprene latex.
[0110] To 40 g of asphalt emulsion PK-1 (manufactured by Toa Road Industry Co., Ltd.) in accordance with JISK 2208-2008, a nonionic surfactant added to chloroprene latex was added in an amount of chloroprene as shown in Table 1, and the mixture was thoroughly mixed to prepare an asphalt composition. CR in Table 1 is chloroprene.
[0111] 40 g of the composition was weighed into a silicon box having a bottom surface of 140 mm×180 mm, and dried under the following conditions to obtain a pitch dry residue.
[0112] This is based on the American Association of State Highway and Transportation Officials (AASHTO) PP72 Edition 2011.
[0113] 25℃×24 hours then 60℃×24 hours
[0114] Next, about 1.00±0.05 g of the dried asphalt residue was weighed into a silicon mold with a hole of 25 mm in diameter and 1.3 mm in depth, heated and melted at 141°C for 15 min, and then cooled at room temperature (25°C) to prepare a test piece of 25 mm in diameter.
[0115] <Oil resistance test>
[0116] About 100 mL of kerosene was placed in a 225 mL glass bottle and the test piece placed on the metal mesh base was immersed in it. At this time, the mass of the metal mesh base and the metal mesh base + test piece was measured and recorded.
[0117] After 1.5 hours at 25°C (room temperature) from the start of immersion, the test piece placed on the metal mesh base was taken out, the kerosene attached to the metal mesh was wiped off, and the mass was measured and recorded. The kerosene attached to the sample was not wiped off.
[0118] The residual rate (%) after 1.5 hours was calculated according to the following formula.
[0119] Residual rate after 1.5 hours (%) = (mass of test piece after 1.5 hours / mass of test piece before immersion) × 100
[0120] <Tetrahydrofuran-insoluble content>
[0121] The amount of tetrahydrofuran insoluble components was calculated by the following formula: Amount of tetrahydrofuran insoluble components (%) = {1-(mass of the residue after volatilization (g) ÷ amount of solid content in 1 g of polymer latex (g))} × 100 (%)
[0122] The mass of the solid content in 1 g of the polymer latex is the mass after 1 g of the latex is dried at 141° C. for 30 minutes.
[0123] [Examples 2-3, Comparative Example 1]
[0124] Chloroprene latex and asphalt composition were prepared and evaluated in the same manner as in Example 1 except that the charge amount of chloroprene monomer was set to the value shown in Table 1 and the amount of chloroprene added in the asphalt composition was set to the value shown in Table 1.
[0125] [Example 4]
[0126] 2.0 kg of 2-chloro-1,3-butadiene (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.6 kg of pure water, 80 g of abietic acid (R-300 manufactured by Arakawa Chemical Industries, Ltd.), 3.6 g of n-dodecyl mercaptan (manufactured by Tokyo Chemical Industry Co., Ltd.), 20 g of 20 mass % potassium hydroxide (manufactured by Wako Pure Chemical Industries, Ltd., special grade product), and 16 g of sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (manufactured by Kao Corporation) were put into a glass reactor having an internal volume of 5 liters, and after emulsification, potassium persulfate (manufactured by Wako Pure Chemical Industries, Ltd., first grade product) was added as a polymerization initiator, and polymerization was carried out at a temperature of 40° C. for 7 hours under a nitrogen atmosphere. The polymerization conversion rate of the monomer was confirmed to be 88%. The polymerization was terminated by immediately adding an emulsion of phenothiazine to obtain a chloroprene latex.
[0127] Then, unreacted monomers were removed by steam distillation. The solid content of the polychloroprene latex was actually measured to be 49.2% by mass.
[0128] An asphalt composition was prepared and evaluated in the same manner as in Example 1 except that the above-mentioned chloroprene latex was used.
[0129] [Examples 5 to 8, Comparative Examples 2 to 6]
[0130] Chloroprene latex and asphalt compositions were prepared and evaluated in the same manner as in Example 4 except that the charge amount and conversion rate of the chloroprene monomer were the values shown in Table 1 and the amount of chloroprene added was the value shown in Table 1.
[0131] [Comparative Example 7]
[0132] An asphalt composition was prepared and evaluated in the same manner as in Example 1 except that chloroprene latex was not used.
[0133] [Comparative Example 8]
[0134] Asphalt compositions were prepared and evaluated in the same manner as in Example 2 except that SBR (styrene butadiene rubber, manufactured by BASF, NX4190) was used instead of the chloroprene latex in Example 1. In Table 1, the column of the amount of chloroprene added indicates the amount of SBR added in Comparative Example 8.
[0135] The results are summarized in Table 1.
[0136]
[0137] The asphalt compositions of the examples all had a residual rate of 88 to 112% after 1.5 hours, with little variation and excellent oil resistance. On the other hand, the results of Comparative Examples 1 to 6, in which the amount of tetrahydrofuran insoluble components and the amount of chloroprene added were outside the protection scope of claim 1, and Comparative Example 7, in which no polymer was used, were: the residual rate after 1.5 hours was less than 60%, and the oil resistance was poor. The result of Comparative Example 8, in which SBR was used instead of chloroprene, was: the residual rate after 1.5 hours was 125%, and the swelled state was poor compared to before the test, and the stability was poor.
[0138] Industrial Availability
[0139] It can be used for asphalt pavement at airports and gasoline stations where oil resistance is required. In addition, it can also provide road pavement that is less likely to cause pits due to fuel leakage, etc. on ordinary roads.
Claims
1. An asphalt composition, characterized in that: It contains asphalt and a chloroprene polymer, wherein the content of the chloroprene polymer is 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the asphalt solid content, and the amount of tetrahydrofuran-insoluble components of the chloroprene polymer is 20% by mass or more and 90% by mass or less.
2. A method for producing an asphalt composition, characterized in that: The asphalt emulsion and the chloroprene latex containing the chloroprene polymer, wherein the amount of the tetrahydrofuran-insoluble component of the chloroprene polymer is 20 mass % or more and 90 mass % or less, are mixed; In the mixing, the mixing amount of the chloroprene latex is calculated as follows in terms of solid content: The chloroprene polymer is contained in an amount of 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the asphalt solid content in the asphalt emulsion.
3. A method for producing an asphalt composition, wherein: The surfactant aqueous solution and chloroprene latex obtained by mixing at 5 to 40° C. are mixed with molten asphalt and emulsified using a colloid mill, wherein the chloroprene latex contains a chloroprene polymer and the amount of tetrahydrofuran-insoluble components of the chloroprene polymer is 20% by mass or more and 90% by mass or less, In the mixing, the chloroprene latex is contained in an amount of 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the asphalt solid content in terms of solid content.
4. The method for producing a composition according to claim 2, wherein: The asphalt emulsion and chloroprene latex are mixed at 5-40°C.
5. The method for producing a composition according to claim 2 or claim 3, wherein: The chloroprene latex used is a chloroprene latex having a stable emulsified state at pH 2 to 4.
6. A method for producing a mixture, wherein: The method comprises the step of mixing the composition obtained by the production method according to claim 2 or 3 with an aggregate.
7. A method for manufacturing an asphalt pavement, wherein: The method comprises the steps of spreading and drying the composition obtained by the production method according to claim 2 or 3.
8. A method for manufacturing an asphalt pavement, wherein: The mixture produced by the production method according to claim 6 is poured.
9. A mixture comprising the composition of claim 1 and an aggregate.
10. An asphalt pavement obtained by spreading the composition according to claim 1 and drying it.
11. An asphalt pavement formed by pouring the mixture according to claim 9.
